Developing and evaluating educational programs for students with autism - Magyar, Caroline I. (Springer eBooks., 2011)
Recent years have witnessed a marked increase both in the number of children diagnosed with autism spectrum disorders (ASDs) and those placed alongside their typically developing peers in general education classrooms. These events bring with them a plethora of challenges, particularly in the areas of program design and educational practices. Developing and Evaluating Educational Programs for Students with Autism offers systematic, evidence-based guidelines,as well as tools, checklists, and other resources?for creating effective learning environments for students across the autism spectrum and the grade span. Planning, development, implementation, and continuous evaluation are examined in detail in this practical volume, which features: An overview of the ASDs, with an emphasis on effective educational practice. In-depth discussion of the ASD Program Development and Evaluation Protocol. A staff training model for personnel working with students with ASD. A detailed framework for student support teams and family-school collaboration. Specific guidelines for conducting needs assessments and student evaluations. Case examples of applications of the protocol on the program, school, and regional levels. Developing and Evaluating Educational Programs for Students with Autism is a uniquely rigorous and thorough reference benefiting school psychologists and special education professionals as well as those in allied educational and mental health fields, including clinical child, school, and developmental psychologists, psychiatrists, and other professionals working with children with autism.